Development and Standardization of a Probiotic-Enriched supplement for CKD - Mohanasundaram, Kowlini; Devarajan, Kalaivani; Janardhanam, Hemamalini Arambakkam (Asian Journal of Biological and Life Sciences)
Introduction: Probiotics are suggested to be potentially therapeutic in the treatment and management of chronic kidney disease (CKD), as they improve gut microbiota, and delay the progression of CKD. Synbiotic benefits are found in Lactobacillus acidophilus and Streptococcus thermophiles, enriched with barely medium (prebiotic), in reducing Blood Urea Nitrogen, Uric acid and creatinine level. Therefore, this study aimed to standardize and develop a probiotic-enriched dietary supplement with barley as the prebiotic base in powdered form, and to prevent uremic toxins by targeting bacterial protein fermentation in gut. Materials and Methods: Half of each vial containing L. acidophilus (MTCC447) and S. thermophilus (MTCC1938) were mixed in 4ml sterile Luria Broth separately and incubated overnight. One ml of each mother culture was transferred to 4ml of selective medium (Nutrient broth) separately and kept for overnight incubation. These two probiotic microorganisms were transferred to prebiotic (enrichment) medium (barley). The colony forming units (CFU) in the enriched nutrient agar medium were counted. The serial dilutions 10-3and 10-6 were selected from the serially diluted culture. The scaled-up microorganisms L. acidophilus and S. thermophilus in the enriched medium were lyophilized. After lyophilisation, cultures were revived and checked for contamination by Gram staining method. CFU were counted to determine the scale-up of the microbes in the enriched medium. Results: There was a significant scale up of the probiotic in the barely medium in the study. Conclusion: Probiotics in barley medium can be used in the management and treatment of CKD, however future studies are required to confirm these findings.
Keywords: CKD; Colony forming units; Lactobacillus acidophilu; Probiotic; Streptococcus thermophilus; symbiotic